Law Enforcement Against Criminal Acts of Subsidized Liquefied Petroleum Gas Abuse in Indonesia - Chandra, Tofik (LifeSciFi, 2023)
Income generated from the oil and gas industry plays a pivotal role in national development. This research adopts a deductive approach, incorporating both the Statute Approach and the Case Approach. The primary objective of this study is to examine the legal aspects of enforcing regulations related to the misuse of subsidized Liquefied Petroleum Gas (LPG) in Jakarta. In response to the significant public demand for oil and natural gas, the government has implemented measures to replace Kerosene with LPG, aiming to reduce fuel subsidies and ease the financial burden on the state. This research is rooted in the Law Enforcement Theory and Punishment Theory, employing a normative juridical approach supplemented by empirical data. The findings reveal that instances of criminal misuse of subsidized LPG gas often involve willing perpetrators without coercion. Consequently, legal consequences are administered in accordance with Article 55 of the Oil and Gas Law and Article 113 of the Trade Law. In a societal context, these actions have adverse consequences, particularly affecting disadvantaged individuals and small-scale businesses, potentially limiting their access to government-regulated subsidized 3-kilogram LPG gas. Therefore, the enforcement of criminal law is deemed an essential measure to address this social issue and ensure compliant distribution of subsidized LPG gas in accordance with prevailing regulations..